2013
DOI: 10.3391/mbi.2013.4.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating high pH for control of dreissenid mussels

Abstract: Two field experiments were carried out using a custom built flow-through laboratory to test the effect of elevated pH on dreissenid musselsas a potential control method. Both experiments tested the ability of dreissenid pediveligers to settle under conditions of elevated pH and thelong-term survival of adult dreissenids under the same conditions. The two experimental sites had different water quality and differentspecies of dreissenids present. The settlement of quagga mussel pediveligers at the lower Colorado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Changes in wastewater constituents during the course of Trial 2 are illustrated in Figure 5-6. The results for DO and pH are shown in Figure 5-7 and were found to be consistent with those observed during Trial 1, where levels remained fairly constant and within the range optimal for zebra mussel viability, even at the time of zebra mussel death (Karatayev et al, 1998;Claudi et al, 2012). From Figure 5-6 it can be seen that the zebra mussels could reduce wastewater constituents from a 1:1 dilution of secondary wastewater.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Changes in wastewater constituents during the course of Trial 2 are illustrated in Figure 5-6. The results for DO and pH are shown in Figure 5-7 and were found to be consistent with those observed during Trial 1, where levels remained fairly constant and within the range optimal for zebra mussel viability, even at the time of zebra mussel death (Karatayev et al, 1998;Claudi et al, 2012). From Figure 5-6 it can be seen that the zebra mussels could reduce wastewater constituents from a 1:1 dilution of secondary wastewater.…”
Section: Resultssupporting
confidence: 76%
“…and an optimum pH range of 7.3 to 9.3. (Karatayev et al, 1998;Claudi et al, 2012). As such, the DO concentrations and pH levels were considered to be within the optimal ranges required for zebra mussel viability in typical freshwater environments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon dioxide also inhibits byssal thread production (McMahon et al 1995;Payne et al 1998; and could prevent settlement of translocators and early life stages. Veliger settlement is reduced in water with pH <7.0 (Claudi et al 2012a(Claudi et al , 2012b, which we achieved with 20 atm PCO 2 at 20°C. Low-level, intermittent infusion of CO 2 could be an effective tool to prevent biofouling and new settlement of dreissenid mussels.…”
Section: Zebra Mussel Responsesmentioning
confidence: 51%
“…The resulting model predicted high mussel mortality (>80%) in a pH range of 6.5 to 8.0 when [Ca 2+ ] was <25 mg L −1 . Conductivity influenced the toxicity of potassium chloride (Moffitt et al 2016) and phosphoric acid (Claudi et al 2012b) to dreissenids and could likewise alter CO 2 toxicity. Claudi et al (2012b) reported approximately 40% mortality of adult quagga mussels after 10-wk exposure to pH 6.9 in lake water with conductivity of 300 to 360 µS cm −1 ; in a follow-up study, adult zebra mussel mortality was minimal after 8-wk exposure to a similar pH in water with 2-fold greater conductivity (613 µS cm −1 ).…”
Section: Native Mussel Responsesmentioning
confidence: 99%